Oman : un sultanat entre mer et désert - Belkaid, Akram; Coatalem, Jean-Luc (Geo magazine, 2011)
Oman fait exception parmi les pétromonarchies du Golfe : il est l'héritier d'une histoire millénaire et prône un islam...
Keywords: Géographie -- Oman

Jughrāfiyyat Wilāyat Shināṣ - Mazrūʿī, Khamīs b. Muḥammad (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)
Keywords: Géographie -- Oman

Jughrāfiyyat Wilāyat al-Muḍaybī - Balūshī, Ibrāhīm b. Ḥasan al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)
Keywords: Géographie -- Oman

Jiyūlūjiyyat wa-Jughrāfiyyat Wilāyat Mirbāṭ - ʿAmrī, ʿAbdallāh. b. ʿAlī al- (Mirbāṭ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Mirbāṭ Yawm al-ithnayn wa’l-thulathā’ 27-28 Shawwāl 1432 H. al-muwāfiq 26-27 Sibtimbar 2011, 2012)
Keywords: Géographie -- Oman

Water and tribal settlement in South-East Arabia: a study of the Aflāj of Oman - Wilkinson, John Craven (Studies on Ibadism and Oman, 2013)
Keywords: Géographie -- Oman